Characterization of nicotinic receptors in chick retina using a snake venom neurotoxin that blocks neuronal nicotinic receptor function - Loring, RH (J Neurosci, 1989)
Nicotinic receptor function has been described in the retinas of a variety of vertebrate species. Neuronal bungarotoxin (NBT, also known as bungarotoxin 3.1, toxin F, or kappa-bungarotoxin) blocks nicotinic receptors in several neuronal preparations, while the neuromuscular antagonist alpha-bungarotoxin (BGT) fails to block most of these receptors. NBT (100 nM), but not BGT (10 microM), substantially blocks nicotinic function on ganglion cells in intact chick retina. 125I-NBT binds to 2 sites in homogenates of chick retina; one site that is shared with BGT (Kd = 5–7 nM, Bmax approximately 500 fmol/retina) and one which is not (Kd = 2–3 nM, Bmax approximately 100 fmol/retina). 125I-NBT binding to the NBT-specific site (binding in the presence of 1 microM unlabeled BGT) is localized to 2 bands in the inner plexiform layer, corresponding to regions richly innervated by neurons containing immunoreactivity for choline acetyltransferase. Furthermore, this binding is blocked by competitive nicotinic agonists and antagonists, but nicotine or other nicotinic agonists do not displace 125I-NBT binding with very high affinity relative to the displacement of 3H- nicotine reported by others in brain. Thus, of the 2 NBT binding sites, the site not recognized by BGT most likely represents functional nicotinic receptors in the chick retina, but these receptors have relatively low affinity for nicotinic agonists, similar to nicotinic receptors found in autonomic ganglia.